Electronic books and DRM - Alonso-Arévalo, Julio; Cordón-García, José-Antonio (Anuario ThinkEPI, 2011)
The emergence of electronic ink, reading devices with legibility levels comparable to paper books, with capacity to store several thousand books, the increase of digital publishing offerings and their increasing presence in publishers´ catalogues, the iPad success with benefits beyond conventional reading, and the emergence of new business models draw an inexorably digital picture in which the issue of copyright protection is essential for the development of the cultural industry. The success of internet business models depends in large measure on systems of digital rights protection. In this context, the development of DRM (Digital Rights Management) has been fundamental and is allowing the management of electronic rights with a certain confidence. This paper discusses DRM systems, their development, the content in which they are applied, and controversies generated in relation to matters such as the right to privacy.
Keywords: DRM; Intellectual property; Publishers; Electronic books; eBooks.